Interdisciplinarity and cultural differences in legal translation - Kozłowska, Joanna (Free your mind: Reflections on language, literature and culture, 2022)
This study is to determine the importance of interdisciplinary perspective on the translation of legal texts. It is suggested that the combined research on jurisprudence and linguistics may contribute to better understanding of legal translation. It is argued that the contrastive work on terminology and law is required in order to explore that field. What is more the author stresses the importance of the cultural differences between legal systems in the process of translating on the example of German-Polish and English-Polish translations.